Analysis of The Content of the Dakwah Message in the Novel "Tinta Terakhir" by Narandara - Syahputri, Siti Novi Astri; Nurhanifah, Nurhanifah (JASNA : Journal For Aswaja Studies, 2024)
The development of modern technology and communications influences the way da'i convey da'wah messages to mad'u. The use of print, electronic and digital media is a necessity and an effective strategy to attract mad'u's attention, enabling the delivery of more exciting and varied messages. One effective method of conveying da'wah messages is through print media such as novels, which, with their literary sentences, can compete with other media in terms of popularity and effectiveness. The purpose of this research is to find out the da'wah messages contained in the novel "Tinta Terakhir" by Narandara. The research uses a qualitative content analysis method, with data taken from dialogue excerpts in the book. The findings of the investigation showed that there were 25 da'wah messages consisting of 4 aqidah messages (1 faith in Allah and three faith in qada and qadar), eight messages regarding sharia including worship (7 prayers and one reading of the Koran), 13 messages regarding morals (6 morals towards Allah, four morals towards fellow humans, and three morals towards family). These findings show that the novel "Tinta Terakhir" can be an effective medium for da'wah by conveying da'wah messages through attractive literary language, able to compete with other media in terms of popularity and effectiveness in conveying da'wah messages.